Personal anticipated information need - H. Bruce (Information Research: An International Electronic Journal)
Background. The role of personal information collections is a well known feature of personal information management. The World Wide Web has introduced to such collections ideas such as filing Web pages or noting their existence in 'Bookmarks' and 'Favourites'. Argument. It is suggested that personal information collections are created in anticipation of some future need for that information-personal, anticipated information need, which also underlies the design of formal information systems. Elaboration. Examination of the literature of information needs and information seeking behaviour leads to the formulation of five propositions that elaborate the concept of personal, anticipated information need. These propositions draw upon concepts such as uncertainty, predictability, sensitivity and the valuation of information sources. Conclusion. An individual's understanding of personal, anticipated information need and how this understanding guides the acquisition and management of personal information will determine the effectiveness of that collection.